Development of kenaf hybrid composite for structural applications - Maleque, Md. Abdul; A., Atiqah; Iqbal, M. (2013)
The main aim of this study is to develop light weight, eco-friendly and cheaper kenaf-glass (KG) fibers reinforced unsaturated polyester hybrid composite on a source of green composite using sheet molding compound process. Unsaturated polyester resin (UPE) and KG fibers in mat form were used at a ratio of 70:30 (by volume) with treated and untreated kenaf fiber.. The hybrid composites were tested for flexural, tensile and Izod impact strength using ASTM D790-03, ASTM D618 and ASTM D256-04 standards respectively. The highest flexural, tensile and impact strength were obtained from treated kenaf with 15/15 v/v KG fibers reinforced UPE hybrid composite in this investigation. Scanning electron microscopy fractrography showed fiber cracking, debonding, fiber pulled-out and fiber tearing as the main fracture mode of composites and kenaf treated 15/15 v/v KG reinforced hybrid composite exhibited better interfacial bonding between the matrix and reinforcement compared to other combinations. Therefore, it can be claimed that the developed hybrid composite is light in weight, cheaper (as kenaf has been used to substitute high cost synthetic glass fibre) and eco-friendly which can be used for structural applications such as automotive, protective helmet, household and construction industry.